2020
DOI: 10.1016/j.celrep.2020.108225
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelinase Disables Inactivation in Endogenous PIEZO1 Channels

Abstract: Summary Endogenous PIEZO1 channels of native endothelium lack the hallmark inactivation often seen when these channels are overexpressed in cell lines. Because prior work showed that the force of shear stress activates sphingomyelinase in endothelium, we considered if sphingomyelinase is relevant to endogenous PIEZO1. Patch clamping was used to quantify PIEZO1-mediated signals in freshly isolated murine endothelium exposed to the mechanical forces caused by shear stress and membrane stretch. Neutral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 63 publications
(117 reference statements)
4
55
0
Order By: Relevance
“…Sphingomyelin (substrates of SMPD3), unlike ceramide, does not influence inactivation but does influence channel force sensitivities. This indicated sphingomyelinase activities, ceramide, and sphingomyelin as regulators of native Piezo gating, which permits prolong activities [72]. In addition to these outstanding findings, Scheuring and colleagues demonstrated that Piezo1 is a springy structure that normally bends the cellular membrane where it lies, but will flatten out when for instance a mechanical force is applied to the cell membrane.…”
Section: Piezo1 Activation and Inactivation Mechanismsmentioning
confidence: 96%
“…Sphingomyelin (substrates of SMPD3), unlike ceramide, does not influence inactivation but does influence channel force sensitivities. This indicated sphingomyelinase activities, ceramide, and sphingomyelin as regulators of native Piezo gating, which permits prolong activities [72]. In addition to these outstanding findings, Scheuring and colleagues demonstrated that Piezo1 is a springy structure that normally bends the cellular membrane where it lies, but will flatten out when for instance a mechanical force is applied to the cell membrane.…”
Section: Piezo1 Activation and Inactivation Mechanismsmentioning
confidence: 96%
“…However, heterologous expression of Piezo1 cDNA from mES cells displays fast inactivation kinetics, indicating that additional regulatory mechanisms other than the amino acid sequence determine the slow kinetics of the Piezo1 channel in mES cells [ 70 ]. Recently, sphingomyelinase activity has been revealed to be a crucial determinant of Piezo1 inactivation [ 71 ]. Various modulators, such as pH, temperature, divalent ion concentrations, alternative splicing, osmotic swelling, membrane lipid composition, co-expression of other membrane proteins, and G-protein-coupled pathways have also been reported to regulate the Piezo channel kinetics [ 55 , 72 79 ]; however, we still know very little about the relationships among these factors and pivotal structural domains.…”
Section: Kinetics Properties Of Piezo Channelsmentioning
confidence: 99%
“…PIEZO1 inactivation is affected by the presence of specific lipids 32,33 , metal ions 30 , disease mutations 34 , as well as external pH 35 , membrane potential 36 , and other unknown cellular factors 37 . In addition to this long list, our study shows that the rate of PIEZO1 inactivation accelerates as more channels open in a patch.…”
Section: Discussionmentioning
confidence: 99%